Distinct m6A methylome profiles in poly(A) RNA from Xenopus laevis testis and that treated with atrazine. (April 2020) - Sai, Linlin; Li, Yan; Zhang, Yecui; Zhang, Juan; Qu, Binpeng; Guo, Qiming; Han, Mingming; Jia, Qiang; Yu, Gongchang; Li, Kaili; Bo, Cunxiang; Zhang, Yu; et al.
Abstract: Recent discovery of reversible N 6 -methyladenosine (m 6 A) methylation on messenger RNA (mRNA) and mapping of m 6 A methylomes in mammals, plant and yeast revealed potential regulatory functions of this RNA modification. However, the role of the m 6 A methylomes in amphibious is still poorly understood. Here, we examined the m 6 A transcriptome-wide profile in testis tissues of Xenopus laevis ( X. laevis ) with and without treatment with 100 μg/L atrazine (AZ) through m 6 A sequencing analysis using the latest Illumina HiSeq sequencer. The results revealed that m 6 A is a highly conserved modification of mRNA in X. laevis . Distinct from that in mammals, m 6 A in X. laevis is enriched around the stop codon and start codon, as is reported in plant. We then investigated the differential expression m 6 A in testes of AZ-exposed X. laevis and compared that with the X. laevis in the control group by m 6 A sequencing. The results indicated that AZ leads to altered expression profile in 1380 m 6 A modification sites (696 upregulated and 684 downregulated). KEGG pathway analysis indicates that the "NOD-like receptors", "tight junction", "Peroxisome proliferator-activated receptors", "adherens junctions", "Glycerophospholipid metabolism" and "Fatty acid biosynthesis" signaling pathways may be associated with abnormal testis development of X. laevis due to exposure to AZ. Analysis results showed a positive correlation between m 6 A modification and mRNA abundance, suggesting a regulatory role of m 6 A in amphibious gene expression. Our first report of m 6 A transcriptome-wide map of an amphibian species X. laevis presented here provides a starting roadmap for uncovering m 6 A functions that may affect/control amphibian testis development. Highlights: m 6 A is a highly conserved modification of mRNA in amphibians compared to human. m 6 A in X. laevis is enriched around the stop and start codon, as is found in plant. A positive correlation between m 6 A modification and mRNA abundance. AZ leads to altered expression profile in 1380 m 6 A modification sites. Six signaling pathways may be related to abnormal testis development of X. laevis.